Natural Products from Chilean and Antarctic Marine Fungi and Their Biomedical Relevance - Arrieche, Dioni; Cabrera-Pardo, Jaime R.; San Martin Barrientos, Aurelio Del Carmen; Carrasco, Hector; Taborga, Lautaro (My University, 2023)
Fungi are a prolific source of bioactive molecules. During the past few decades, many bioactive natural products have been isolated from marine fungi. Chile is a country with 6435 Km of coastline along the Pacific Ocean and houses a unique fungal biodiversity. This review summarizes the field of fungal natural products isolated from Antarctic and Chilean marine environments and their biological activities.
Keywords: marine natural products; marine fungi; chilean marine fungi; biological activities